Kajian Etnomedicine Tumbuhan Obat Antiinflamasi Pada Masyarakat Samin Kecamatan Margomulyo Bojonegoro - Yaya Sulthon Aziz; Nadia Hasna (Jurnal Farmasi & Sains Indonesia, 2021)
The use of medicinal plants is mostly done by tribes in Indonesia, one of them is the Samin tribe. Information on the use of medicinal plants can be done using ethnopharmaceutical methods. This research was conducted to determine the use of plants as anti-inflammatory drugs, how to manufacture, how to use plants as anti-inflammatory drug ingredients in the tribe of Samin, and to obtain UV and ICF values based on bioprospective analysis. Determination of the informants in the Samin tribe with the Snowball sampling method, followed by semi-structured interviews. Bioprospective analysis of plants that have the potential to be anti-inflammatory. Bioprospective parameters tested were UV, ICF. ICF values are used to identify the most important disease categories and are used as parameters in plant species for further research. UV value which is the most widely used plant and high level of confidence for treatment. Obtained 11 types of anti-inflammatory diseases, 28 anti-inflammatory plants. There were 6 anti-inflammatory diseases including broken bones with a value of 1, stung by bees 1, mumps 0.75, scratch wounds 0.75, uric acid 0.33, and toothache 0.33. The results of the ICF values above, then obtained plants used for anti-inflammatory treatment with the highest UV values are betel 0.91, bitter 0.83, black taro 0.83, breadfruit 0.5, and greetings 0.5. The five plants that need further research are the black taro plant, for which there is no research that discusses more deeply, so the black taro plant is a potential source of new anti-inflammatory.,